Pengembangan Media Pembelajaran Bahasa Arab Berbasis Audio Visual Untuk Meningkatkan Maharah Istima’ Pada Siswa-Siswi Madrasah Ibtidaiyah - Tri Tami Gunarti (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
In every learning process learning media is an important thing needed, therefore as a teacher must be able to prepare good learning media so that lessons can be absorbed and understood easily by students, especially when the material being taught is related to foreign languages, in terms of this is Arabic. Arabic which is taught to students, especially in madrasah Ibtidaiyyah children, certainly has several learning outcomes, including maharah kalam and maharah Istima ', thus to improve Maharah Istima' (listening skills) in Arabic learning, good learning media are needed. so that Arabic teaching and learning activities run well and efficiently. In the era of globalization, technology is increasingly developing and advanced, automatically learning media develops, namely by utilizing information technology in the field of audio-visual media as a medium for learning Arabic. Audio-visual based Arabic learning media has become the demands of the times, although making Arabic language learning media based on audio-visual requires special skills, it does not mean that the use of these media is avoided and abandoned by Arabic teachers or teachers.